Բյուջետային ծախսերի սոցիալ-տնտեսական նշանակությունը և դրանց արդյունավետության բարձրացման խնդիրները - Վ. Բ. Բոստանջյան (ՀՀ ԳԱԱ հրատ.)
Расходная политика, проводимая правительством РА, обусловлена возможностью определения степени оптимальности размера государственного сектора и уровня бюджетных расходов, способствующих решению возникших в стране социально-экономических проблем. The paper is devoted to the analysis of the expenditure policy implemented by the Armenian government over the last fifteen years in order to determine the current optimality of public sector and extent of contribution of the budgetary expenditures at solving state social and economic problems.
Keywords: H Social Sciences; Economic Theory